DIALECTAL COMPARISON BETWEEN SIMARASOK SUB-DIALECT AND PADANG TAROK SUB-DIALECT: THE LEXICAL VARIATION - Tesa Anjelia; Rusdi Noor Rosa (Universitas Negeri Padang, 2019)
Geography and social life were two main causes of why a language has the variation. One of them is lexical variation The purpose of this research was (1) to identify the lexical similarities between Simarasok sub-dialect and Padang Tarok sub-dialect (2) to identify the lexical differences between Simarasok sub-dialect and Padang Tarok sub-dialect. In this research, the researcher used descriptive method; it is possible to compare two sub-dialects so the researcher can find the similarities of vocabularies, the lexical variation and the uniqueness of lexical changes. From the research that has been done, the researcher used 200 words of swadesh list and 100 words of basic vocabularies to see the lexical similarities and differences that exist between Simarasok sub-dialect and Padang Tarok sub-dialect. From the data, the researcher found the similarities of vocabularies used between Simarasok sub-dialect and Padang Tarok sub-dialect. The differences or the lexical variation that found in Simarasok sub-dialect and Padang Tarok sub-dialect are caused by the affixation, derivation, borrowing from other languages and blending. From this paper the researcher hope that this paper can be useful in learning as an additional knowledge in learning Dialectology.